Nutritional Health Programmes in India: How far have we reached? - George, Sylvia; Chandrakar, Aditi; Giri, Anjan Kumar (Indian Journal of Community Health, 2025)
The vicious cycle of poverty and undernutrition in India has been a crippling criterion to the development of the nation. Health being a fundamental right, it falls upon the government to make sure the citizens are well nourished. Hence, there is a need for National Health Programmes with a specific focus on nutrition. Over time, India has come up with numerous programmes with focused objectives on nutrition. Some have seen significant success, like the Goitre Control Programme and the Integrated Child Development Service Project, while others are still struggling to meet their targets at least halfway, like the Nutritional Anaemia Programme. The latest and the most elaborate initiative by the government of India, Poshan Abhiyaan, stands out in its convergence and community mobilisation strategies. It puts the vulnerable population in the spotlight, under-five children and expectant or nursing mothers. The holistic approach described in the programme is a game changer in the approach to nutrition as far as India is concerned. The programme is right now gaining much attention in the post pandemic era as the country’s magnum opus to be, among health programmes, in the near future.